Analyzing the Correlation of Government Support Efforts to Franchise in MEA for Indonesia's Economic Progress - Yuwono, Excel Febrianka; Urbaniasi, Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
There are lots of very diverse new businesses that offer different types of products and services, such as modern food and beverage businesses. The franchise business concept makes it possible for someone who has material capital but lacks experience in building their own business to have a profitable business, especially if you buy a franchise from a well-known brand. The purpose of this study is to analyze the correlation of franchise with the input of labor support in dealing with the MEA and to analyze the role of the government in franchise support in the substance of the MEA. regarding the franchise in facing MEA and how the government contributes in it. The industry contribution to the franchise sector is very large because it can absorb a lot of labor, with a large number of workers absorbed increasing economic growth in Indonesia, franchises are able to survive the monetary crisis because franchises produce products that are directly consumed, not depending on capital from banks, to produce goods selectively based on consumption needs, franchise generally comes from termination of employment.